Understanding Associations Between Hurricane Harvey Exposure and Mental Health Symptoms Among Greater Houston-Area Residents. (February 2020) - Bevilacqua, Kristin; Rasul, Rehana; Schneider, Samantha; Guzman, Maria; Nepal, Vishnu; Banerjee, Deborah; Schulte, Joann; Schwartz, Rebecca M.
ABSTRACT: Objective: Hurricane Harvey made landfall on August 25, 2017 and resulted in widespread flooding in Houston and the surrounding areas. This study aimed to explore the associations between exposure to Hurricane Harvey and various mental health symptoms. Methods: Self-reported demographics, hurricane exposure, and mental health symptomatology were obtained from residents of the greater Houston area through convenience sampling for a pilot study, 5 months after the storm from January 25-29, 2018 (N = 161). Results: Increased hurricane exposure score was significantly associated with increased odds for probable depression, probable anxiety, and probable posttraumatic stress disorder after adjusting for other factors associated with mental health. No significant associations were found between demographic characteristics and risk of mental health difficulties. Conclusions: Mental health difficulties associated with exposure to Hurricane Harvey were still present 5 months after the storm. Future disaster response programs should focus on providing long-term mental health services to hurricane survivors.